The Effect of Primary Phase Grain Refinement of Al-Si alloys on heat cracking. Issue 1 (August 2020) - Bubenko, M.; Molnar, D.; Monika, T.; Fegyverneki, Gy.
Abstract: In this research thermal analysis was carried out for different alloys which use for gravity die cast cylinder heads. The experiments were implemented under industrial conditions. The aim was to examine the effect of the small amount of supplementary grain refining pre-alloy on primary crystallization for hot-crackings. Different evaluating methods of thermal analysis were tested and compared. Results proved that the dosing small amount of grain refining alloy is favorable in the foundry production practice.